PENGARUH RASIO LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM - Arya Darmawan Darmawan (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2016)
This study is performed to examine the effect of Current Ratio (CR), Quick Ratio (QR), Debt to Equity Ratio (DER), Return on Equity (ROE) and Earning per Share (EPS toward the Stock Pricing in mining companies that is listed in BEI.( Bursa Efek Indonesai Data used in the research originated from audit annual financial statements. The sampling method is purposive sampling. It is gained sample amount of 7 minging companies from 37 companies.From the analysis result, it indicates that CR, DER, and EPS variable partially significant toward Stock Pricing of the company in BEI on 2009-2013 period on the level of significance less than 5%, while it indicates that QR and ROE partially not significant toward Stock Pricing. While simultaneously Current Ratio (CR), Quick Ratio (QR), Debt to Equity Ratio (DER), Return on Equity (ROE) andEarning per Share (EPS) proof significantly influent Stock Pricing in mining companies BEI in the level less than 5%. Predictable of the five variables toward Stock Pricing is 80%, as indicated by R square that is 80% while the rest 20% is affected by other factors is not included into the study model.